Islam dan Rasionalitas dalam Wacana Digital: Analisis Wacana Kritis Norman Fairclough terhadap Konten YouTube Raymond Chin - Indah Fitria Nilna Azizah; Zaenal Sukawi (PT Anugerah Literasi Indomedia, 2026)
The development of digital media has changed the pattern of Islamic da'wah from a conventional approach to a digital discourse that is multimodal and dialogical. However, the practice of digital da'wah is still often dominated by emotional narratives with minimal rational argumentation. This condition raises the need for a study that highlights how Islamic rationality is constructed in the digital da'wah space. This study uses a qualitative method with Norman Fairclough's Critical Discourse Analysis (AWK) approach which includes three dimensions of analysis, namely text, discourse practice, and socio-cultural practice. Primary data is in the form of YouTube Escape Episode 13 content entitled